Residual strength of chopped strand mat glass fibre/epoxy composite structures: Effect of temperature and water absorption - Jeffrey K.J.T.; Tarlochan F.; Rahman M.M. (Universiti Malaysia Pahang, 2023)
The residual strength of chopped strand mat glass fibre/epoxy composites following exposure to different hygrothermal conditions was investigated. All residual tests were carried out according to ASTM D 3479 and D 3039 on tension-tension fatigue with a frequency of 5 Hz, a stress ratio of R= 0.5and maximum stress ?max = 60 MPa. The residual strength curves were used to investigate the strength of chopped strand mat glass fibre/epoxy under the effect of temperature and the interactive environment of water absorption and temperature. The results showed that the chopped strand mat glass fibre/epoxy had high resistance toward tension-tension fatigue loading. However, the degradation of the tensile residual strength of chopped strand mat glass fibre/epoxy was significant with high water absorption at an elevated temperature. Universiti Malaysia Pahang.